2017
DOI: 10.1007/s00392-017-1079-0
|View full text |Cite
|
Sign up to set email alerts
|

Implantable cardioverter/defibrillators for primary prevention in dilated cardiomyopathy post-DANISH: an updated meta-analysis and systematic review of randomized controlled trials

Abstract: Our meta-analysis of all available randomized evidence shows a survival benefit of ICD therapy for primary prevention in DCM. DANISH results suggest an attenuation of this ICD advantage when compared to contemporary medical and cardiac resynchronization therapy. Until larger trials have confirmed this finding, ICD therapy should remain the recommendation for primary prevention of SCD in DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 50 publications
0
21
0
3
Order By: Relevance
“…4 Even though an updated meta-analysis on ICD trials still showed that ICD implantation is effective, it shows that these recommendations cannot be rightfully extrapolated to those with non-ischaemic DCM. 4,5 Over the past years, many studies described risk factors for ventricular arrhythmias in non-ischaemic DCM. These studies uniformly reported previous sustained ventricular arrhythmias and late gadolinium enhancement (LGE) on cardiac magnetic resonance imaging (cMRI) as important predictors of arrhythmic events.…”
Section: Introductionmentioning
confidence: 99%
“…4 Even though an updated meta-analysis on ICD trials still showed that ICD implantation is effective, it shows that these recommendations cannot be rightfully extrapolated to those with non-ischaemic DCM. 4,5 Over the past years, many studies described risk factors for ventricular arrhythmias in non-ischaemic DCM. These studies uniformly reported previous sustained ventricular arrhythmias and late gadolinium enhancement (LGE) on cardiac magnetic resonance imaging (cMRI) as important predictors of arrhythmic events.…”
Section: Introductionmentioning
confidence: 99%
“…Die Indikation zur ICD-Primärprävention bei nicht ischämisch bedingter Herzinsuffizienz wurde durch die DANISH-Studie [56] infrage gestellt, in der eine primärpräventive ICD-Implantationunabhängig von einer gleichzeitigen CRT-Implantationnicht zu einer signifikanten Mortalitätsreduktion führte [56], auch wenn in einer späteren Metaanalyse ein Nutzen des ICD in dieser Patientengruppe weiterhin nachweisbar war [57]. Nach der aktuell noch gültigen ESC-Leitlinie zur Herzinsuffizienz (in der die DANISH-Studie noch nicht berücksichtigt war) besteht bei diesen Patienten zwar weiterhin eine Klasse-I-Indikation zur ICD-Implantation.…”
Section: Therapieunclassified
“…119,120 The mortality can also be reduced for selected patients with HFrEF of non-ischemic etiology, but the evidence is ambiguous. [121][122][123][124] However, current guidelines recommend implantation of an ICD since the evidence is more in favor for implantation than withholding ICD. 1 ICD is not indicated for patients with severe symptoms, such as physical status of NYHA IV that is refractory to medical therapy, not eligible for MCS or Htx.…”
Section: Device Treatment For Heart Failure Implantable Cardioverter mentioning
confidence: 99%